2009
DOI: 10.1194/jlr.d800055-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive quantification of ceramide species in human stratum corneum

Abstract: This article is available online at http://www.jlr.org novo pathways, such as alterations of some species of the targeted lipidomes into others. Similar to common quantitative analyses using direct MS or LC-MS that need authentic standards together with internal ones, quantitative lipidomics may also require a standard set of all lipid species targeted, because each lipid species has a different molar response in MS detection except for special cases. However, it is practically impossible to obtain all authent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
152
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(158 citation statements)
references
References 46 publications
5
152
0
1
Order By: Relevance
“…4, it can be concluded that the mass range of this newly identifi ed CER [EOdS] ranges from m/z 1015.0 to 1181.1 amu and corresponds exactly with a CER [EOdS], having a total chain length ranging from 66 to 78 carbon atoms long. Besides, it is known from literature that the CERs containing an even number of carbon atoms are more abundantly present than odd chain length CERs ( 21,23 ), which is also the case in our mass spectrum of Fig. 4 , again confi rming that the unknown CER subclass is CER [EOdS].…”
Section: Cer Analysis Of a Human Skin Explant Modelmentioning
confidence: 48%
See 3 more Smart Citations
“…4, it can be concluded that the mass range of this newly identifi ed CER [EOdS] ranges from m/z 1015.0 to 1181.1 amu and corresponds exactly with a CER [EOdS], having a total chain length ranging from 66 to 78 carbon atoms long. Besides, it is known from literature that the CERs containing an even number of carbon atoms are more abundantly present than odd chain length CERs ( 21,23 ), which is also the case in our mass spectrum of Fig. 4 , again confi rming that the unknown CER subclass is CER [EOdS].…”
Section: Cer Analysis Of a Human Skin Explant Modelmentioning
confidence: 48%
“…Future studies will include several of these standards to make this assay (semi-) quantitative. The use of several nonisotopically labeled internal standards to correct for chain length and CER subclass regarding human SC is described in the literature only once ( 23 ).…”
Section: Profi Ling Of Cers In Synthetic and Biological Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, ceramides in the normal stratum corneum play an important role in maintaining the moisture and barrier functions of the skin [15,16]. Ceramides in the stratum corneum are classified into phytosphingosine-type, sphingosine-type and dihydrosphingosinetype [17][18][19]. Therefore, we investigated the effect of miso extracts on the expression of enzymes for ceramide synthesis and on the activity of the enzymes that were specifically induced by miso extracts.…”
mentioning
confidence: 99%